do you mean -3/(4x) -2 = -8
or
-3/4 * x -2 = -8
because, as it is written, (using pmdas) it is the latter.
-3/4x-2=-8
-3/4 x= -8 +2 = -6
x = (-4/3)*(-6) = 8
If the former, then
-3/(4x) - 2 = -8
-3/(4x) = -6
-3 = (-6)*4x
-3 = -24x
x = 1/8
2006-11-13 11:23:33
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
To solve the equation for X you need to isolate X.
1) add 2 to both sides of the equation, this will yield: -3/4X = -6
2) divide both sides by -3/4, this will yield:
X = -6/-3/4 which is the same as:
X = (6) (4/3) = 24/3 = 8
So, X equals 8
Now, substitute 8 for X in the original equation to see if we got the correct answer:
(-3/4)(8) -2 = -24/4 -2 = -6 -2 = -8!
Hope this helps. Good luck.
2006-11-13 11:29:52
·
answer #2
·
answered by Doctor J 7
·
0⤊
0⤋
assuming that you meant (-3/4)x - 2 = -8 then
add 2 to both sides
(-3/4)x = -6
then multiply both sides by (-4/3)
x = 8
if you meant -3/(4x-2) = -8 then
multiply both sides by (4x-2)
-3 = (4x-2)(-8)
distribute the -8
-3 = -32x + 16
add both sides by 32x and 3
32x = 19
x = 19/32
im assuming you meant the first one so the answer is
8
2006-11-13 11:28:59
·
answer #3
·
answered by trackstarr59 3
·
0⤊
0⤋
add 2 to each side
-3/4x-2+2=-8+2
then multiply each side by -4/3
-4/3(-3/4x)=-6(-4/3)
x=-8
2006-11-13 11:30:04
·
answer #4
·
answered by twilightstar210 2
·
0⤊
0⤋
yeah, your answer is either 8 or 1/8 depend on how you write the question.
Change your question by editing it
2006-11-13 11:29:52
·
answer #5
·
answered by tdbhc33 2
·
0⤊
0⤋
-3/4x=-8+2
-3/4x=-6
3/4x=6
4x=3/6
4x=1/2
x=1/8
2006-11-13 11:23:38
·
answer #6
·
answered by Dupinder jeet kaur k 2
·
0⤊
0⤋